Peranan Kualitas Produk dan Diskon Produk pada Pengaruh Live Streaming terhadap Perilaku Impulsive Buying pada Aplikasi TikTok - Eriska Kurnia Arum; Algifari; Bianka Andriyani (LPPM STIE YKPN Yogyakarta, 2025)
The aim of this research is to examine the role of product discounts and product quality in the influence of live streaming on impulsive buying behavior within the TikTok application. This study employs a quantitative approach, collecting data through a questionnaire distributed via Google Forms to respondents aged 12 to 27 who are consumers of TikTok e-commerce. This research used 106 respondents as samples. The analysis results indicate that live streaming does not effect to impulsive buying on Gen Z in Yogyakarta. This research suggests that despite online sales through live streaming, the phenomenon of impulsive buying does not occur. Live streaming that implemented by e-commerce owners on TikTok has no effect to Gen Z's purchasing decisions, who tend to shop rationally while watching live streams. Additionally, the quality of products and discount products offered during live streaming does not moderate effects impulsive buying behavior to Gen Z in Yogyakarta.